Performance of broilers fed water-soluble blood meal during growing and finishing period - Habib, MA; Shahidullah, M; Ali, MA (Bangladesh Veterinarian, 2010)
The effect of water-soluble blood meal was tested on the performance of broilers. Forty broiler chickens aged 21 days were reared on slatted floor and the dietary treatments were T0, T1, T2 and T3 where 0, 0.25, 0.50 and 0.75 g blood meal was given/L drinking water, respectively. The blood meal significantly enhanced the growth and feed conversion efficiency. The weight gain and net profit was significantly (p<0.001) higher in chickens with 0.25g/L blood meal in water. It is suggested that blood meal at 0.25g/L may be used in drinking water during growing and finishing period of broilers for better performance. DOI: 10.3329/bvet.v26i1.4625 Bangl. vet. 2009. Vol. 26, No. 1, 8-12